Highly Stable Inverted Organic Solar Cell Structure Using Three Efficient Electron Transport Layers - Mohamed El Amine Boudia; Zhao Cunlu (Energies)
The efficiency of organic solar cells (OSCs) is influenced by various factors, among which environmental temperature plays a significant role. Previous studies have shown that the thermal stability of these cells can be enhanced by incorporating a third component into their structure. Ternary organic solar cells, particularly, have shown promising results in improving thermal stability. A well-designed electron transport layer (ETL) can significantly bolster thermal stability by facilitating efficient charge transport and reducing charge recombination. In this study, we investigated the effect of temperature, ranging from 300 K to 400 K, on the efficiency of inverted ternary structures by using a one-dimension optoelectronic model on “Oghma-Nano 8.0.034” software. The structures examined include (S1) “FTO/SnO2/PM6:D18:L8-BO/PEDOT: PSS/Ag”, (S2): “FTO/C60/PM6:D18:L8-BO/PEDOT: PSS/Ag”, and (S3): “FTO/PC60BM/PM6:D18:L8-BO/PEDOT: PSS/Ag”. Simulations using three different ETLs—SnO2, C60, and PC60BM—at 340 K (66.85 °C) resulted in a main effect on open circuit voltage (Voc) and fill factor (FF) values, in addition to an important Jsc value in terms of thermally stable devices. However, these structures retained 92% of their initial ~20% efficiency observed at 300 K, demonstrating significant thermal stability under high power conversion efficiency (PCE) conditions.